[La(ηx-Bx)La]− (x = 7–9): a new class of inverse sandwich complexes. Issue 8 (15th January 2019) - Chen, Teng-Teng; Li, Wan-Lu; Li, Jun; Wang, Lai-Sheng
Abstract : Photoelectron spectroscopy and computational chemistry reveal that lanthanide elements can form a class of novel inverse sandwich complexes consisting of aromatic B7, B8, and B9 monocyclic rings. Abstract : Despite the importance of bulk lanthanide borides, nanoclusters of lanthanide and boron have rarely been investigated. Here we show that lanthanide–boron binary clusters, La2 B x −, can form a new class of inverse-sandwich complexes, [Ln(η x -B x )Ln] − ( x = 7–9). Joint experimental and theoretical studies reveal that the monocyclic B x rings in the inverse sandwiches display similar bonding, consisting of three delocalized σ and three delocalized π bonds. Such monocyclic boron rings do not exist for bare boron clusters, but they are stabilized by the sandwiching lanthanide atoms. An electron counting rule is proposed to predict the sizes of the B x ring that can form stable inverse sandwiches. A unique (d-p)δ bond is found to play important roles in the stability of all three inverse-sandwich complexes.